BUCKETING STRATEGIES FOR EFFICIENT TRIANGLE DETECTION IN CAM-SYSTEM BASED ON FACETED MODELS - Gandjar Kiswanto; Rahmat Widyanto; Priadhana Edi Kresnha (Faculty of Computer Science - Universitas Indonesia, 2010)
Triangle’s checking in 3D faceted models is an essential step in gouging detection and elimination process. To check whether model surface intersects the tool, every triangle in the model has to be checked. Unfortunately, this process takes much time. Since the computer can’t see and doesn’t know which triangles located under the current tool position, then the triangles all over the surface model should be checked. To reduce the time, region checking at every position of tool has to be detected. Triangles that have to be checked are only in that region. The way of creating the region can be done by bucketing. Bucketing process will make some buckets as representation of regions and each bucket will be filled with triangles that lie in the corresponding region. There are several bucketing methods. This paper will explain all methods which have been implemented in the research. Pengecekan segitiga dalam model 3 dimensi berfaset merupakan tahapan penting dalam deteksi gouging dan proses eliminasi. Untuk mengecek apakah permukaan model bersinggungan dengan alat, setiap segitiga pada model harus diperiksa. Akan tetapi, proses ini membutuhkan waktu yang lama. Segitiga-segitiga pada seluruh permukaan model harus diperiksa karena komputer tidak dapat melihat dan tidak mengetahui segitiga mana yang terletak di bawah posisi alat saat ini. Untuk mengurangi konsumsi waktu, pengecekan wilayah pada setiap posisi alat harus dapat dideteksi. Segitiga yang harus diperiksa adalah hanya yang berada pada wilayah tersebut. Cara yang dapat dilakukan untuk menetapkan wilayah adalah dengan menggunakan bucketing. Proses bucketing akan membuat beberapa bucket sebagai representasi dari beberapa wilayah dan setiap bucket akan diisi dengan segittiga yang terletak pada wilayah terkait. Terdapat beberapa metode bucketing. Paper ini akan menjelaskan semua metode yang telah diimplementasikan di dalam riset.